Indirect and non-medical economic burden, quality-of-life, and disabilities of the myelofibrosis disease in Spain. (June 2014) - Gimenez, Emmanuel; Besses, Carles; Boque, Concepcion; Velez, Patricia; Kerguelen, Ana; Cervantes, Francisco; Ferrer-Marin, Francisca; Perez-Encinas, Manuel; Rodriguez, Mercedes; Gonzalez, Juan Diego; Calzada, Reyes; Hernandez-Boluda, Juan Carlos
Abstract Introduction: Myelofibrosis is a non-frequent chronic myeloproliferative Philadelphia-negative chromosome neoplasm. It is a heavy incapacitating orphan disease and associated with high morbidity and mortality. In this context, indirect and non-medical costs are expected to be high. The main objective of this project is to estimate the economic burden of this disease in Spain. Methods: Thirty-three patients with a diagnosis of myelofibrosis for at least 1 year participated in a questionnaire in three Spanish centers. The study consisted of analyzing in various aspects the cost and impact of the disease; indeed, daily life time limitations with a need of informal care, symtomatology. Additionally, information concerning the clinical management of the disease was collected through a focus group of eight experts. Results: The mean age was 65 years. 15 of 33 patients were at their productive stage. Six had difficulties at work and eight have received informal care. Bone and muscular pain were the main symptoms of patients (72%). The estimated global indirect and non-medical costs of the disease were 86, 315€ per patient (20% working and 80% informal care), which reached 104, 153€ at productive stage patients (45%) and 168, 459€ for more symptomatic patients. Conclusions: The economic burden of indirect and non-medical costs of myelofibrosis are important (15, 142€/annual) as a result, and should be considered in economic evaluation, as well as in preventive plans for patients and caregivers, despite the fact that studies with larger numbers of patients should be done.